2019
DOI: 10.1002/jsfa.9852
|View full text |Cite
|
Sign up to set email alerts
|

Protein digestion properties of Xinong Saanen goat colostrum and mature milk usingin vitrodigestion model

Abstract: BACKGROUND Xinong Saanen goat milk is a raw material for goat milk‐based infant formula production. This study aims to analyze digestion properties of Xinong Saanen goat colostrum and mature milk by simulating infant gastrointestinal digestion. Zeta potential, particles size, protein profile and peptides composition of these two kinds of milk during the digestion process were studied. RESULTS Zeta‐potential values of the digested colostrum were lower than those of mature milk through the whole digestion. Absol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 31 publications
(49 reference statements)
1
7
0
Order By: Relevance
“…This might be caused by the fact that a smaller particle size resulted in higher surface activity, leading to the phenomenon of particle aggregation (Ye et al, 2010). A similar phenomenon was reported that particle size of both types of milk showed an initial decrease, and then an increase throughout the digestion process (Sun et al, 2019).…”
Section: Resultssupporting
confidence: 81%
“…This might be caused by the fact that a smaller particle size resulted in higher surface activity, leading to the phenomenon of particle aggregation (Ye et al, 2010). A similar phenomenon was reported that particle size of both types of milk showed an initial decrease, and then an increase throughout the digestion process (Sun et al, 2019).…”
Section: Resultssupporting
confidence: 81%
“…The reduction of ζ-potential of the digested TM may be related to the change of its conformation and surface components after hydrolysis. In addition, it may be attributed to the action of enzymes and bile salts in the digestive fluids …”
Section: Resultsmentioning
confidence: 99%
“…Changes in the surface charges of CN and fat globules can promote digestive speed, so zeta potential measurements are suitable to characterize the surface charge changes in these particles and the digestion efficiency of milk (33). When the absolute value of the zeta potential is greater than 30 mV, the digestive system has good electrostatic stability (34). The zeta potentials of the three brands of infant formula showed similar trends during digestion (Table 1).…”
Section: The Absolute Zeta Potentials Of Protein and Lipid Surfaces I...mentioning
confidence: 92%